Optimization of Social Media as a Marketing Tool at PT. Indonesian Travel Amanah - NY, Erlina Satri; Widodo, Slamet (Sinergi International Journal of Economics, 2024)
This research aims to find out how to optimize social media as a marketing tool at PT. Amanah Travel Indonesia, a company that focuses on Umrah travel services. The research method used is qualitative research with a research design, namely a case study. The research results show that the use of social media such as Instagram, Facebook, and YouTube is very effective in increasing brand awareness, interaction with potential congregants, and sales. An interesting content strategy, consistent posting, and active interaction with the audience are proven to strengthen relationships with customers. This research confirms the importance of integrating various social media elements to achieve optimal marketing effectiveness.